Wujud Makna Pragmatik Tindak Tutur Imperatif Dalam Film Keluarga Cemara Dan Implementasinya Sebagai Bahan Ajar Bahasa Indonesia Kelas Viii Smp - Putri, Aswa Tamkinati; , Drs. Andi Haris Prabawa, M.Hum (2017)
Aswa Tamkinati Putri/ A310130064. PRAGMATIC MEANING FORM OF IMPERATIVE SPEECH IN KELUARGA CEMARA FILM AND ITS IMPLEMENTATION AS RESPECTIVE MATERIAL IN BAHASA INDONESIA AT 8th GRADE STUDENTS OF JUNIOR HIGH SCHOOL . Research Paper. Teacher Training and Education Faculty, Muhammadiyah Surakarta University. June 2017. This study aims to describe the form of pragmatic meaning of imperative speech in Keluarga Cemara film and its implementation as respective material of Basic Competence 3.3 in Junior High School. Primary data has been collected during research phase by observing technique. This study used "See involve able" method following with recording technique by noting. Data analysis technique being implemented is matching technique method. The result in this study are as follows : (1) There are 60 forms of pragmatic meaning in Keluarga Cemara film. (2) There are 10 data of pragmatic imperative language , 9 verbs of orders, 5 verb of demanding, 1 verb of whishes, 5 verbs of insistence, 3 verbs of persuasion, 1 verbs of appeal, 2 verbs of inviting, 3 verbs of solicitation, 2 verbs of permission request, 2 verbs of allowing, 5 verbs of prohibition, 3 verbs of hope, 5 verbs of swearing, 1 verb of congratulating, 2 verbs of advice, 1 verb of praising.